Elimination of Bisphenol A and Triclosan Using the Enzymatic System of Autochthonous Colombian Forest Fungi (2013)
ABSTRACT: Bisphenol A (BPA) and triclosan (TCS) are known or suspected potential endocrine disrupting chemicals (EDCs) which may pose a risk to human health and have an environmental impact. Enzyme preparations containing mainly laccases, obtained from Ganoderma stipitatum and Lentinus swartzii, two autochthonous Colombian forest white rot fungi (RF), previously identied as high enzyme producers, were used to remove BPA and TCS from aqueous solutions. A Box-Behnken factorial design showed that pH, temperature, and duration of treatment were significant model terms for the elimination of BPA and TCS. Our results demonstrated that these EDCs were extensively removed from 5 mg L−1 solutions aer a contact time of 6 hours. Ninety-four percent of TCS and 97.8% of BPA were removed with the enzyme solution from G. stipitatum; 83.2% of TCS and 88.2% of BPA were removed with the L. swartzii enzyme solution. Aer a 6-hour treatment with enzymes from G. stipitatum and L. swartzii, up to 90% of the estrogenic activity of BPA was lost, as shown by the yeast estrogen screen assay. 2,2-Azino-bis-(3-ethylthiazoline-6- sulfonate) (ABTS) was used as a mediator (laccase/mediator system) and significantly improved the laccase catalyzed elimination of BPA and TCS. e elimination of BPA in the absence of a mediator resulted in production of oligomers of molecular weights of 454, 680, and 906 amu as determined by mass spectra analysis. e elimination of TCS in the same conditions produced dimers, trimers, and tetramers of molecular weights of 574, 859, and 1146 amu. Ecotoxicological studies using Daphnia pulex to determine lethal concentration (LC50) showed an important reduction of the toxicity of BPA and TCS solutions aer enzymatic treatments. Use of laccases emerges thus as a key alternative in the development of innovative wastewater treatment technologies. Moreover, the exploitation of local biodiversity appears as a potentially promising approach for identifying new efficient strains for biotechnological applications.